A Conceptual Model for Growth and Decay of the Cordilleran Ice Sheet - Fulton, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTA conceptual model for growth and decay of the Cordilleran Ice Sheet has evolved over 100 years of Quaternary research in British Columbia. Physiography and location relative to prevailing westerly winds were the main factors controlling the style of glacier build up. The pattern of decay was controlled mainly by physiography. With cooling at the beginning of glaciation, mountain glaciers expanded to become valley glaciers and eventually coalesced on adjacent plateaus or shelves to form an ice sheet. At glacial maximum, this sheet extended from the western margin of the continental shelf to the eastern edge of the Rocky Mountains and from the Columbia Plateau to the central Yukon. The central (highest) part of the ice sheet was hemmed in by mountains, consequently, snowline had to rise nearly to its present elevation before shrinking of the central core could begin. This meant that mountain glaciers which initiated growth of the ice sheet were reduced to near their present dimensions before significant recession could take place in the core area of the ice sheet. As a consequence, large ice masses in the interior of British Columbia stagnated and then shrank to remnants occupying major valleys and eventually were reduced to dead ice blocks buried in glacial debris. This pattern of retreat contrasts with that of ice masses centred on mountain blocks, such as the Alps, where rising of the snowline resulted in recession of ice cap margins back towards original accumulation areas in the central core of the mountains.